EQUATION OF STATE OF WATER BASED ON SPEEDS OF SOUND MEASURED IN THE DIAMOND-ANVIL CELL - Abramson E.H.; Brown J.M. (My University, 2004)
Measurements of the speed of sound in water have been extended to 5.5 GPa and 400°C. The data were taken in the diamond-anvil cell using Impulsive Stimulated Scattering (Forced Rayleigh Scattering) at acoustic frequencies of ∼1 GHz. Measured sound speeds differ significantly from those given by previously published equations of state; at 5 GPa, measured speeds are 3% lower than those predicted by the 1995 formulation of the International Association for the Properties of Water and Steam (IAPWS). New thermal diffusivity measurements to 1 GPa are combined with previously reported thermal conductivities in a determination of specific heat. A complete equation of state (giving all thermodynamic quantities) was generated and subsequently extended to 40 GPa and 3000 K. This equation of state matches both our speed of sound data and previously published shock wave data; in a range extending to 3 GPa and 700–1600°C predicted densities are up to 5% higher than those reported from studies of inclusions, leading to a reinterpretation of those previous studies. Within the range of the new data, an experimentally determined estimate of uncertainty is given for the densities.